An analytical study of contemporary educational issues contained in the websites of educational research and studies centers - Maudud, Mohammed; Diallo, Souleyman; Alharthi, Abdulrahman Mohammed Nafeez (Journal of Educational and Psychological Sciences, 2023)
This study aimed at clarifying some of contemporary educational issues found on the websites of research and study centers, such as (Baraeen Center, Dalail Center, and Takween Center). Where the researchers studied the educational issues that are expected by analyzing the content of the websites of the centers, using descriptive analytical approach in order to achieve the research objective. The research consists two aspect, theoretical framework and the practical aspect. After analyzing the websites, the researchers reached a number of results, including: Educational research and studies centers contain some contemporary educational issues, where the research came across (11) issues that were considered as contemporary educational issues, and these issues are as follows: The issue of authenticity and Modernity- which means Paying attention to the original identity and keeping pace with modern scientific development-The challenges of women’s education, women’s employment, drug issues, challenges of intellectual deviation, Atheism challenges, Technology and media challenges, feminism, homosexuality, terrorism, and the challenges of globalization. The issue of (atheism) ranked first among contemporary educational issues with a percentage of (57.81%), it was mentioned (855) times. Then the issue of drugs which was mentioned (132) times with a rate of (8.92%), followed with the issue of intellectual deviation that ranked third position with a percentage of (6.42%), mentioned (95) times.